269OEfficacy and safety of isatuximab plus pomalidomide and dexamethasone in East Asian patients with relapsed/refractory multiple myeloma: A subgroup analysis of ICARIA-MM study. (24th November 2019) - Ikeda, T; Sunami, K; Huang, S-Y; Wang, M-C; Koh, Y I; Min, C G; Yeh, S-P; Matsumoto, M; Uchiyama, M; Iyama, S; Shimazaki, C; Lee, J H; et al.
Abstract: Background: The phase 3 ICARIA study demonstrated that isatuximab (Isa) plus pomalidomide and dexamethasone (Pd) significantly improved progression free survival (PFS) compared with Pd in patients (pts) with relapsed/refractory multiple myeloma (RRMM) (HR = 0.596, 95%CI 0.44-0.81, P = 0.001). We evaluated the efficacy/safety of Isa-Pd in the East Asian pts (13 Japanese, 9 Korean and 14 Taiwanese pts) of ICARIA. Methods: RRMM pts who had received ≥2 prior lines of therapies, including lenalidomide (len) and at least a proteasome inhibitor (PI), and were refractory to their last therapy were enrolled. Pts were randomized into either Isa-Pd arm who received Isa 10 mg/kg IV weekly for the first 4 weeks (wks) followed by biweekly or Pd arm, and all pts received Pom (4mg PO days 1-21) and dex (40mg [20mg if older than 75 yrs] PO or IV weekly) in 28 day cycle until disease progression or unacceptable toxicity. Results: Data from 36 East Asian pts (21 Isa-Pd, 15 Pd) including Japanese pts (9 Isa-Pd, 4 Pd) were analyzed. Patient's characteristics were similar in the East Asian subgroup and the entire population of ICARIA study (n = 307). Of these pts, median age: 65 (range, 41-85) yrs; median prior lines of therapy: 3 (range, 2-7); 91.7% and 69.4% were refractory to len and PI, respectively; and 13.9% had high-risk cytogenetics. After median follow-up of 11.6 months, median PFS was not reached yet in Isa-Pd arm and was 7.9 months in Pd arm (HR 0.517 [95% CI 0.19-1.39]). ORR (≥PR) was 71.4% in Isa-Pd arm 60% in Pd arm. The VGPR rate or better was 61.9% and 13.3% in Isa-Pd and Pd arm, respectively. Median time to first response was 32 days and 59 days for Isa-Pd and Pd arm, respectively. Grade ≥3 AEs were observed in 90.5% and 73.3% pts in Isa-Pd and Pd arm, respectively and which caused 9.5% pts in the Isa-Pd arm and 0 % in Pd arm to discontinue their treatment. Infusion associated reactions were reported in 57.1% pts receiving Isa-Pd but none of them were grade 3-4. Conclusions: This subgroup analysis of ICARIA demonstrates that the efficacy and safety of Isa-Pd in East Asian population, including Japanese pts, are comparable with the entire population of ICARIA. Isa-Pd is a novel treatment option for East Asian pts with RRMM. Clinical trial identification: Clinical trial information: NCT02990338. Legal entity responsible for the study: Sanofi. Funding: Sanofi. Disclosure: K. Sunami: Speaker Bureau / Expert testimony: Sanofi; Speaker Bureau / Expert testimony: Novartis; Speaker Bureau / Expert testimony: GlaxoSmithKline; Speaker Bureau / Expert testimony: Janssen Pharmaceutical. M. Matsumoto: Speaker Bureau / Expert testimony: Celgene Co., LTD; Speaker Bureau / Expert testimony: Janssen Pharmaceutical Co., LTD; Speaker Bureau / Expert testimony: Bristol-Myers Squibb K.K.; Speaker Bureau / Expert testimony: Ono Pharmaceutical Co., LTD. C. Shimazaki: Speaker Bureau / Expert testimony: Ono Pharmaceutical Co. Ltd.; Speaker Bureau / Expert testimony: Celgen Co. Ltd.; Speaker Bureau / Expert testimony: Fujimoto Pharmaceutical Co. Ltd. F. Campana: Full / Part-time employment: Sanofi. K. Tada: Full / Part-time employment: Sanofi. S. Iida: Speaker Bureau / Expert testimony: Ono; Speaker Bureau / Expert testimony: Janssen; Speaker Bureau / Expert testimony: Celgene; Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Speaker Bureau / Expert testimony: Takeda; Speaker Bureau / Expert testimony: Novartis; Speaker Bureau / Expert testimony: Daiichi-Sankyo; Speaker Bureau / Expert testimony: Chugai; Speaker Bureau / Expert testimony: Kyowa Hakko Kirin; Speaker Bureau / Expert testimony: Sanofi; Speaker Bureau / Expert testimony: MSD; Speaker Bureau / Expert testimony: Daiichi Sankyo; Speaker Bureau / Expert testimony: Gilead; Speaker Bureau / Expert testimony: AbbVie. K. Suzuki: Speaker Bureau / Expert testimony: Janssen; Speaker Bureau / Expert testimony: Novartis; Speaker Bureau / Expert testimony: Celgene; Speaker Bureau / Expert testimony: Ono; Speaker Bureau / Expert testimony: Fujimoto; Speaker Bureau / Expert testimony: Takeda; Speaker Bureau / Expert testimony: Sumitomo Dainippon ; Speaker Bureau / Expert testimony: BMS; Speaker Bureau / Expert testimony: Sanofi. All other authors have declared no conflicts of interest.